Estudo da interação entre o oxigênio molecular com complexos tetraazamacrociclos de cobalto utilizando a Teoria do Funcional da Densidade - Lima, Leidiana de Sousa (2016)
This paper presents the results obtained by quantum study applying the functional theory of density - DFT and using the B3LYP functional to verify the electronic structures of Tetraazamacrociclos Cobalt (CoN4) and their interactions with oxygen through Griffith adsorption models (Side-on) and Pauling (End-on). The initial structures of Porphyrin Cobalt complex – CoP, Octametilporfirina Cobalt - CoOMP, Tetrametilporfirina Cobalt - CoTMP, tetraaza [14] annulene Cobalt - CoTAA and Dibenzotetraaza [14] annulene Cobalt - CoDBTAA were obtained from GaussView program and optimization the geometry and charge distribution of the structures, as well as their interactions with molecular oxygen were carried out using the Gaussian 09 program. The results shows that the structure of the macrocycle ligands influence O2 binding capacity to cobalt. In evaluating the interaction with oxygen, porphyrin cobalt and its derivatives showed better evidence against group tetraaza [14] annulene, for interaction with molecular oxygen due to weakening of the bond in the O2 molecule characteristic enhanced by data from Mulliken charge. Therefore, the order of interaction presented by the studied complexes is CoTMP, CoOMP, CoP, CoDBTAA and CoTAA in End-on model and CoP CoOMP, CoTMP, CoDBTAA and CoTAA in side-on model.